Co‐Joined Starch Modification and β‐Carotene Dispersion In Situ by Planetary Ball Milling. (25th June 2020) - González, Luciana Carla; Loubes, Maria Ana; Santagapita, Patricio Román; Tolaba, Marcela Patricia
Abstract: The objective is to evaluate An innovative dispersion method (IM), planetary ball milling (PBM) is evaluated for its potential use in obtaining starch modifications together with in situ β‐carotene dispersion. Native (N) and ball milled (BM) rice starches are first evaluated as encapsulating matrices of β‐carotene, by means of traditional dispersion method (TM) using a rotor–stator device. Ball milled starch with gelatin (BM+G) preserves β‐carotene structure and produces the highest encapsulated β‐carotene content (0.154 mg g −1 ), being four times the N starch content (0.035 mg g −1 ). By IM, β‐carotene structure is partially (69%) preserved by using the BM+G matrix. Encapsulated β‐carotene contents >86% (equivalent to 0.50 mg g −1 starch) and encapsulated/surface ratio >6.7 are achieved, obtaining at least 3.0‐ and 16.3‐fold increments compared to TM, respectively. Results from IM reveal the potential of PBM to reach a high degree of β‐carotene dispersion in a physically modified starch improving the encapsulation performance with respect to TM. Abstract : An innovative method to obtain starch modifications and β‐carotene dispersion in situ is tested by planetary ball milling. β‐carotene structure is partially (69%) preserved, a 16‐fold increase in the encapsulated/surface ratio and a threefold increase in the encapsulated β‐carotene content are obtained compared to traditional rotor–stator homogenizers.